Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.1002/pol.1980.180181112
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution NMR spectra and phase equilibria in poly(phenylacetylene)‐diluent mixtures

Abstract: The C‐13 NMR spectra of partly crystalline poly(phenylacetylene) (PPA) in CDCl3 CCl4 are rather well resolved and the peaks can be matched with those of 1, 3,5‐triphenylbenzene. A different, less‐well‐resolved C‐13 spectrum is characteristic of a disordered PPA obtained by heating. We conclude that crystalline PPA has the chain conformation of a cis‐cis‐oid helix. This interpretation is consistent with the proton NMR spectra and is supported by the fluorescence spectra, which can display two bands, one conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Hexagonal polymer chains packed in a column are also conjectured to be rotated in each column where the molecular axis distance, i. e., the c-axis, cannot be estimated because of being effectively an infinite one 36) . The helicoidal 1 a polymers with a rigid and rodlike structure have been postulated by Ehrlich and his group 37) . They reported that the crystalline 1a polymer which was repeatedly treated with a mixture of CDCl 3 and CCl 4 displayed birefringence due to a liquid crystallike order, although the crystalline structure of the 1 a polymer has not been identified by them.…”
Section: Formation Of Columnar Polymermentioning
confidence: 95%
See 1 more Smart Citation
“…Hexagonal polymer chains packed in a column are also conjectured to be rotated in each column where the molecular axis distance, i. e., the c-axis, cannot be estimated because of being effectively an infinite one 36) . The helicoidal 1 a polymers with a rigid and rodlike structure have been postulated by Ehrlich and his group 37) . They reported that the crystalline 1a polymer which was repeatedly treated with a mixture of CDCl 3 and CCl 4 displayed birefringence due to a liquid crystallike order, although the crystalline structure of the 1 a polymer has not been identified by them.…”
Section: Formation Of Columnar Polymermentioning
confidence: 95%
“…It appears that the polymer chains which are packed in the hexagonal column may be helical chains which stabilize the columnar structure. The helical structure of the 1 a polymer has been described by Sanford et al 37) , Simionescu et al 46) , and recently by us 19) using molecular mechanic calculations. The calculations support that the cis-transoid structure of 1 a polymer is helical as has been previously deduced.…”
Section: Aggregation Of Radical Spinsmentioning
confidence: 97%
“…In the MO calculations, we take account of not only planar zigzag configurations such as cis-transoidal, trans-cisoidal, and transtransoidal forms, but also the same deflected configurations as the TGЈTGЈ-type for the trans chain in poly(vinylidene fluoride) reported by Hasegawa et al 19 The cis-cisoidal forms of the chain was not used in the calculation, because the steric hindrance of phenyl groups in PPA chain did not allow the considerable helical structure of the chain. 6,8,17 Figure 1 shows the backbone geometry of the same deflected trans chain conformation projected on a perpendicular plane and a perpendicular axis to its axis. The deflected angle of corresponds to the dihedral angle between two double bonds in the main chain.…”
Section: Molecular Orbital Calculationsmentioning
confidence: 99%
“…The two kinds of 13 C peaks in the spectrum of deflected trans-PPA are attributed from the phenyl group and the main chain, because pyrolysis byproducts of triphenylbenzene and low molecules were removed completely. 6,17 Comparing the respective peaks of the deflected trans-PPA with those of the cis-PPA, peak 1 shifts downfield by 0.24 ppm, but peak 2 becomes broader and shifts upfield by 3.07 ppm. Table I lists the chemical shift values of the two peaks and the respective chemical shift variations, ⌬␦s, for cis-and deflected trans-PPAs.…”
Section: Cp/mas Spectrum Of Ppamentioning
confidence: 99%
“…During the past two decades, bidentate rhodium complexes, for example, [Rh(nbd)Cl] 2 (nbd: norbornadiene), Ziegler–Natta catalyst, Fe(acac) 3 ‐AlH( i ‐Bu) 2 , Luttinger's catalyst, RhCl 3 ‐LiBH 4 , Wilkinson's catalyst, RhCl(PPh 3 ) 3 , and metathesis catalysts such as WCl 6 or MoCl 5 , have been developed as important stereoregular polymerization catalysts for phenylacetylene (PA) together with other substituted acetylene (SA) monomers to obtain substituted polyacetylenes (SPA)s, which are known to have helical cis ‐ transoid structures. Furthermore, the propagation species, that is, a monodentate Rh species from the bidentate Rh complex catalyst, has been generated in situ when triethylamine (TEA), alcohol, or aqueous alcohol was used as a cocatalyst or as the polymerization solvent .…”
Section: Introductionmentioning
confidence: 99%